DNA binding and photo-induced DNA cleavage activity of Elsinochrome A in visible light. Issue 4 (2011) - Ma, Fei; Tang, Jing; Yang, Chao; Feng, Yu-Ying; Wei, Shao-Hua; Shen, Jian; Zhou, Jia-Hong; Zhou, Lin
Abstract : The interaction of Elsinochrome A (EA) with calf thymus DNA (CT-DNA) has been investigated by UV-vis spectra and fluorescence spectra. The results show that EA can bind with CT-DNA and binding sites are destroyed after irradiation by visible light, which indicates that EA is a promising candidate for photodynamic therapy. In addition, the binding mechanism is studied using fluorescence quenching test and ethidium bromide (EB) replace assay experiments. The results suggest that EA and CT-DNA are binding with a strong force and the major binding mode of EA with DNA could be the electrostatic binding.